Penerapan Clinical Pathways sebagai Instrumen Pengendalian Biaya Pelayanan : Studi Penelitian Tindakan Penderita BPJS yang Menjalani Operasi Caesar dengan Sistem Pembayaran INA-CBG - Annisa Fitria; Andri Sofa Armani; Thinni Nurul Rochmah; Bangun Trapsila Purwaka; Widodo Jatim Pudjirahardjo (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of using clinical pathways to control total actual hospital costs for BPJS patients who undergo a cesarean section. The method used in this research is action research. The results showed that the average actual hospital costs were significantly higher after the application of CP with p = 0.019. The average length of stay, service costs, and hospital costs were significantly lower in the entire CP form group with p = 0.012, p = 0.013, and p = 0.012. In conclusion, this study shows that the application of clinical pathways can reduce the length of hospitalization and actual hospital costs for cesarean section patients and indicates that clinical pathways can make services more efficient. Keywords: Hospital Costs, Clinical Pathway, Caesarean Section